The Implementation of Islamic Values and Local Wisdom in Preserving the Dhikr Tradition on Students at SMA Negeri 1 Batudaa Pantai - Mokoagow, Friska; Yahiji, Kasim (Jurnal Ilmiah Iqra', 2024)
The Implementation of Islamic Values and Local Wisdom in Preserving the Dhikr Tradition on Students at SMA Negeri 1 Batudaa Pantai. This research has two problems: How is the Implementation of Islamic values and local wisdom at SMA Negeri 1 Batudaa Pantai, and how is the implementation of the preservation of dhikr on local wisdom at SMA Negeri 1 Batudaa Pantai? The type of research used was qualitative research with observation and documentation methods. The research data sources include primary data and secondary data. Data collection techniques used are data reduction, data presentation, and verification.The results indicated that Islamic and local wisdom values were related to the curriculum objectives implemented at school, such as religious values, tolerance, cooperation, peace, love, and environmental care. It was associated with applying Islamic values through local wisdom, which is carried out through History learning that connects material with regional culture and direct practice. Local wisdom is defined as the wealth and wisdom of life; a tradition cannot survive if the community, government, and school do not cooperate in its preservation. The preservation of dhikr (dikili) is to make people aware, especially millennials who will be the successors of a tradition. The dzikir (dikili) tradition is often carried out yearly before commemorating the Maulid of the Prophet Muhammad SAW.